Legal Provision of Social Protection of Employees in the Conditions of Martial Law - Vakariuk, Liudmyla (м. Дніпро, 2023)
Purpose. To study changes in legal provisions regarding social protection of employees because of legal restrictions put into effect during martial law. To develop recommendations for clarifying the legal provisions of specified restrictions. To propose ways and directions of strengthening protection of the social rights of employees (SRE). Methodology. General and special methods of cognition are used: hermeneutic method – for the interpretation of legal provisions of legislative acts, which regulate legal provision of SRE; analysis and synthesis – to study changes in legal provision of SRE; induction and deduction – to develop recommendation on clarifying the legal provisions of normative restrictions on SRE: analytical, formal legal and special legal methods – to determine the ways and directions of strengthening protection of SRE. Findings. The changes in the legal framework for the protection of SRE because of legal restrictions put into effect during martial law are studied and presence of some inconsistencies in legal provisions is indicated, which requires clarification of new legal concepts and the application of indicating norms. The need for a wellfounded implementation of a dispositive approach to rules for protection of SRE is pointed out and as well as for an imperative approach to the rules that the employer must follow. It is proposed to weaken the tendency to oust collective agreements from the legal field. Normalization of feedback between legislators and public organizations and trade unions is proposed. Originality. Insufficiency of the legal conditionsindicators in normativelegislative field regarding introduction of SRE narrowing and limitation of the legal possibilities for their protection are pointed out. Recommendations to clarify the legal provisions of regulatory restrictions of SRE are developed. Ways and directions of strengthening the protection of SRE are proposed. Practical value. The introduction of indicating norms and the implementation of the proposed recommendations will contribute to the strengthening of SRE protection.
Keywords: legal support, social protection of employees, conditions of martial law, the regulatory and legal field